Diurnal Rhythm in Anticoagulant Effect of Heparin during a Low Dose Constant Rate Infusion - Krulder, J W M; de Boer, A; van den Besselaar, A M H P; Cohen, A F; Schoemaker, H C; Briët, E; Meinders, A E (Thrombosis and Haemostasis, 1992)
The objective of the study was to investigate possible diurnal rhythms in coagulation tests during a continuous intravenous infusion of unfractionated heparin. Six volunteers participated in the study, which was divided in a treatment (500 U heparin/h for 30 h) and a control experiment. Under basal conditions, no rhythm was found in coagulation tests. During heparin treatment, APTT, thrombin clotting time and anti-Xa activity showed a greater anticoagulant effect at night, with a striking decrease in the morning.In a search for the explanation of this phenomenon we looked for diurnal variations in the urinary excretion of heparin, in the plasma concentrations of antithrombin III and platelet factor 4, and in the effect of heparin added to the plasma samples in vitro. None of these studies provided the explanation.